2003
DOI: 10.1177/000992280304200309
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Cystic Lung Disease: Diagnostic and Therapeutic Considerations

Abstract: Congenital lung cysts such as congenital cystic adenomatoid malformation, pulmonary sequestration, congenital lobar emphysema, and bronchogenic cysts are rare but fascinating anomalies of lung development. While there are many similarities in terms of their presenting features, there are particular differences between the diagnostic groups that are important to highlight, especially in relationship to approaches to imaging and long-term outcome. A case of each entity is presented with an emphasis on the contem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 77 publications
0
39
1
Order By: Relevance
“…Interestingly, there is little in the literature suggesting that CBA accounts for CCLD [11][12][13][14]. We believe the discrepancy between the previous reports and this series attribute to difficulties in pathological diagnosis of CBA.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Interestingly, there is little in the literature suggesting that CBA accounts for CCLD [11][12][13][14]. We believe the discrepancy between the previous reports and this series attribute to difficulties in pathological diagnosis of CBA.…”
Section: Discussioncontrasting
confidence: 70%
“…It has been reported that CBA frequently affects the left upper lobe and is incidentally diagnosed in asymptomatic young adults [1,4,5]. However, there are only a few case reports of CBA diagnosed in childhood [6][7][8][9][10], and there is little in the literature suggesting that CBA accounts for congenital cystic lung disease (CCLD) [11][12][13][14]. Here, we describe the clinical and pathological characteristics of CBA in infants and children.…”
mentioning
confidence: 99%
“…1 Herein, we describe the unusual case of an infant whose airway symptoms were the result of a bronchogenic cyst. 1 Herein, we describe the unusual case of an infant whose airway symptoms were the result of a bronchogenic cyst.…”
Section: Introductionmentioning
confidence: 99%
“…Conclusion: The addition of fentanyl to epidural infusions of bupivacaine in infants undergoing thoracotomy for resection of CCAM may prolong recovery and increase the incidence of adverse respiratory events without providing a significant analgesic benefit. D 2005 Elsevier Inc. All rights reserved.Congenital cystic adenomatoid malformation (CCAM) of the lung is a rare condition that often requires thoracotomy in infancy for resection of the abnormal lung tissue [1]. The technique of choice at the Children's Hospital of Philadelphia for postoperative pain management in these patients is 0022-3468/$ -see front matter D…”
mentioning
confidence: 99%
“…Congenital cystic adenomatoid malformation (CCAM) of the lung is a rare condition that often requires thoracotomy in infancy for resection of the abnormal lung tissue [1]. The technique of choice at the Children's Hospital of Philadelphia for postoperative pain management in these patients is 0022-3468/$ -see front matter D…”
mentioning
confidence: 99%